The indicative influence of oxidative stress on low milk yields in dairy cattle - Witaya Suriyasathaporn (2018)
The goal of this study was to identify the correlation between milk yield and milk malondialdehyde (MDA), an oxidative stress marker. The study was conducted using cows from eight small-holder dairy farms during October to December 2004. The data comprised of sample date, milk yield, and the recent calving date were recorded. Morning milk samples were collected monthly for the measurement of somatic cell counts (SCC) and MDA level using the automate counter and the modified Smith's method, respectively. The final data set included 131 milk data from 74 cows. Overall means and SEM of milk yields, somatic cell scores (SCS, the normalize transformation of SCC data), MDA and days in milk were 14.5±0.45 kg/day, 2.97±0.19, 1,643±26 ppb, and 154.8±8.83 day, respectively. The average milk yields ranged from 9.7±2.0 to 17.7±0.9 kg/day. Results from Pearson's correlation coefficients show that MDA, SCS and days in milk were negatively associated with milk yield (p<0.05). In multiple linear regression analysis, only MDA and days in milk were significantly associated with milk yields. The study indicates that the loss of milk yield after intramammary infection may be highly mediated by increased oxidative stress status.